TINJAUAN PELAKSANAAN PELAYANAN PRIMA PADA BANK BTN KCP CIAMIS - Nunung Nurhayati; Annisa Desty Puspatriani (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2026)
This study is motivated by the importance of implementing excellent service in improving service quality in banking institutions. Good service is one of the important factors in creating a positive corporate image and providing convenience for customers in conducting various banking transactions. The purpose of this study is to determine the implementation of excellent service, the obstacles encountered in its implementation, and the efforts made to overcome these obstacles at Bank BTN KCP Ciamis. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation involving employees engaged in the customer service process. The research was conducted by directly observing service activities provided by employees to customers in the workplace. The results show that the implementation of excellent service at Bank BTN KCP Ciamis has been carried out fairly well, as indicated by the friendly, polite, and responsive attitudes of employees in providing services, as well as their ability to deliver clear information regarding banking products and services. However, in practice there are still several obstacles. Based on preliminary observations at Bank BTN KCP Ciamis, customer service has not yet been fully optimal. At certain times, customers or developers who arrive at the beginning of operational hours still have to wait because services at the Consumer Loan Sales (CLS) section cannot be provided immediately. In addition, services at the Teller Service and Customer Service sections often continue during employees’ break time, causing the break schedule not to always be followed. This condition indicates that the responsiveness aspect of service still needs to be improved so that services can run more effectively and efficiently.